Rapid Syntheses of (−)‐FR901483 and (+)‐TAN1251C Enabled by Complexity‐Generating Photocatalytic Olefin Hydroaminoalkylation. Issue 6 (30th December 2019) - Reich, Dominik; Trowbridge, Aaron; Gaunt, Matthew J.
Abstract: We report a common strategy to facilitate the syntheses of the polycyclic alkaloids (−)‐FR901483 (1 ) and (+)‐TAN1251C (2 ). A divergent synthetic strategy provides access to both natural products through a pivotal spirolactam intermediate (3 ), which can be accessed on a gram‐scale. A photocatalytic olefin hydroaminoalkylation brings together three readily available building blocks and forges the majority of the carbon framework present in 1 and 2 in a single operation, leading to concise total syntheses. The complexity‐generating photocatalytic process also provides direct access to novel non‐racemic spirolactam scaffolds that are likely to be of interest to early‐stage drug discovery programs. Abstract : The speed of light : The syntheses of polycyclic alkaloids (−)‐FR901483 and (+)‐TAN1251C through a common spirolactam intermediate are reported. Photocatalytic olefin hydroaminoalkylation brings together three readily available building blocks to produce the majority of the carbon framework in one step, leading to concise total syntheses.